Problemy w procesie komunikacji między nauczycielem, a uczniem z niepełnosprawnością w dobie pandemii COVID-19 - Adamczyk, Katarzyna (Zeszyty Naukowe Pedagogiki Specjalnej, 2022)
The topic of the following paper will be communication problems between teacher and student with disabilities in the era of COVID – 19 pandemic Based on the results of the survey, we can draw conclusions and implications surrounding remote learning, which has now been and continues to be the only form that replaces traditional classroom instruction for students during Coronavirus.